Analisis Clash Detection Perencanaan Proyek X Untuk Meminimalisir Anggaran Biaya dan Waktu - Natalia, Monika; Misriani, Merley; Hamid, Desmon; Zulfajri, Muhammad; Iskandar, Arjunda (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Project construction has complexity conflict (clash). Clash can cause work delays, design changes, additional material, cost overruns, reduced quality, and project delays. Clash construction design can be detected with Autodesk Revit and Autodesk Naviswork manage software which are part of building information modeling (BIM) software. This research found the clash detection Project of X, caused this project's potential clash to be very large because each component is designed by a different team, so when detail engineering design (DED) it intersects with each other component. This study aims to find clash detection (hard clash and soft clash) for structural, architectural mechanical, electrical, and plumbing (MEP) components and provide solutions by repairing the clash. Hard clash found 184 clash points consisting of: clash between structures and architecture with 9 points, structures and MEP with 59 points, architecture and architecture with 16 points, architecture and MEP with 11 points, and MEP and MEP with 89 points. Soft clash found 96 points consisting of: clash between structures and architecture with 52 points, structures and MEP with 1 point, architecture and architecture with 18 points, architecture and MEP with 3 points, and MEP and MEP with 22 points. The solution to the clash found is to change, remove, and add to the components that occur clash using Autodesk Revit, to get zero clash so that this project planning is free clash.